2020
DOI: 10.1063/5.0015374
|View full text |Cite
|
Sign up to set email alerts
|

Tuning plasmonic field enhancement and transients by far-field coupling between nanostructures

Abstract: We study how the collective effects of nanoparticles arranged in rectangular arrays influence their temporal plasmon response and field enhancement property. By systematically changing the lattice constant for arrays containing identical metal nanorods, we experimentally demonstrate how grating induced effects affect the position and, more importantly, the broadening of extinction spectra. We correlate these effects with the achievable field enhancement and the temporal duration of plasmon transients and formu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…By comparing the experimental results with the values calculated (Calculations were made by using the MiePlot computer program, available at www.philiplaven.com/mieplot.htm (accessed on 3 March 2023)) for individual spherical nanoparticles in the relevant composition and size range, one can conclude that the measured values follow the theoretical trend reasonably well. However, the peak positions measured on the nanostructure layers are consistently larger than those of the individual nanoparticles, which indicates coupling between the particles forming the deposited layer [56,57]. Since aggregation of the particles is apparent in Figure 3, such deviation from the theoretical trend is expected.…”
Section: Optical Propertiesmentioning
confidence: 90%
“…By comparing the experimental results with the values calculated (Calculations were made by using the MiePlot computer program, available at www.philiplaven.com/mieplot.htm (accessed on 3 March 2023)) for individual spherical nanoparticles in the relevant composition and size range, one can conclude that the measured values follow the theoretical trend reasonably well. However, the peak positions measured on the nanostructure layers are consistently larger than those of the individual nanoparticles, which indicates coupling between the particles forming the deposited layer [56,57]. Since aggregation of the particles is apparent in Figure 3, such deviation from the theoretical trend is expected.…”
Section: Optical Propertiesmentioning
confidence: 90%
“…Especially, when the pitch size of the array is close to the specific value d c = λ SP / n (where, λ SP is plasmon resonance wavelength and n is the refractive index of the surroundings), the constructive radiative interactions are induced between neighboring nanostructures, leading to a narrower plasmon resonance band compared to that of the isolated nanostructure. , In contrast to the dark plasmon modes, far-field coupling can be easily induced by fabricating periodic arrays of the metallic nanostructures. To date, some groups have reported that the extinction or scattering spectral features of plasmons can be modified by adjusting the periodicity of the arrays, suggesting that the plasmon dephasing time can be extended by far-field coupling. However, in the case of the periodic arrays of nanostructures, their spectral characteristics, such as peak wavelength and bandwidth, are seriously modulated by the diffraction or interference effects arising from their periodic spatial arrangement. Therefore, for the arrayed nanostructures, it is difficult to accurately evaluate their plasmon dephasing time from the conventional extinction or scattering spectral measurements, and the temporal confinement effect of light on the arrayed nanostructures remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%